2011
DOI: 10.2507/ijsimm10(2)3.176
|View full text |Cite
|
Sign up to set email alerts
|

Flexible manufacturing systems modelling and performance evaluation using AutoMod

Abstract: In recent times flexible manufacturing systems emerged as a powerful technology to meet the continuous changing customer demands. Increase in the performance of flexible manufacturing systems is expected as a result of integration of the shop floor activities such as machine and vehicle scheduling. The authors made an attempt to integrate machine and vehicle scheduling with an objective to minimize the makespan using Automod. Automod is a discrete event simulation package used to model and simulate a wide vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…• web enabled product configuration tool, so that customers can configure its products in the meaning of choosing the material, customizing design and choosing special features, • implementation of ERP and PDM/PLM systems for an easier understanding of customer needs, product and process data management, information sharing and collaboration, analyses and corrective measures [27], • the development of software solution for part groups creation and scheduling in a customized production environment, • RFID part tagging, so that every part can be tracked throughout its "life" in a shop floor, and in the warehouse, • different manufacturing process execution scenarios simulation [29] and [30], for the prediction of possible problems and the evaluation of solutions, • integration of previously mentioned tools and systems through heavy use of XML data representation, a similar solution can be found in the work of Šormaz et al [28].…”
Section: Discussionmentioning
confidence: 99%
“…• web enabled product configuration tool, so that customers can configure its products in the meaning of choosing the material, customizing design and choosing special features, • implementation of ERP and PDM/PLM systems for an easier understanding of customer needs, product and process data management, information sharing and collaboration, analyses and corrective measures [27], • the development of software solution for part groups creation and scheduling in a customized production environment, • RFID part tagging, so that every part can be tracked throughout its "life" in a shop floor, and in the warehouse, • different manufacturing process execution scenarios simulation [29] and [30], for the prediction of possible problems and the evaluation of solutions, • integration of previously mentioned tools and systems through heavy use of XML data representation, a similar solution can be found in the work of Šormaz et al [28].…”
Section: Discussionmentioning
confidence: 99%
“…[11] Pandey R and Singh A obtained the graph before and after introducing of AGV in the system and plotted percentage utilization of AGVs and machines in FMS environment concluded that job production was improved with increase in efficiency of the whole system. [12] Reddy B.S.P. and Rao C.S.P.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Simulation is a commonly accepted tool in improving manufacturing facilities and processes [12][13][14][15][16]. Discrete event simulation (DES) is very accurate and it can capture virtually any level of production detail.…”
Section: Objectives Of Our Simulation Studymentioning
confidence: 99%
“…In addition, Kaban et al [12] demonstrated how to use simulation to solve job shop scheduling problems. A simulation model to evaluate the performance and the flexibility of manufacturing systems has been provided by different authors [13][14][15]. Manufacturing system design problems have been solved by several other authors using simulation [16].…”
Section: Introductionmentioning
confidence: 99%